SYNTHESIS OF ANGLE AND RANGE MEASURER IN TRACK-WHILE-SCAN SUPER-FAST BEAM SCANNING SYSTEMS - S. V. Anikeev; V. A. Kurenjov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The method of angle measurement in super-fast scanning (SFS) systems is presented. The SFS range cells scanning allows to get the angle information from envelop of received pulses dwell time. Complex information processing of SFS and range cell scanning in synthesized two dimensional measurer is employed.